Analysis of the evolution of defects in tunnels in the city of Recife-PE (Research, Society and Development, 2022)
Preventive maintenance is essential for the good performance of any engineering work, especially when it comes to special works of art (OAEs). The most recent tunnels in the city of Recife have shown intense defects, with the same degree of risk as their older counterparts, and measures must be taken care of. The objective of the work is to visually inspect the tunnels and transmit the evolution, between 2017 and 2021, of the problems arising from lack of maintenance and defects of the Abolition and Felipe Camarão Tunnels. Through bibliographical research, it was possible to obtain data on the levels of conservation from four years before and, thus, carry out a comparative analysis. From the inspections, it was evident that the underpasses in question related to maintenance failures and defects: vandalism and graffiti, water percolation with landfill material carrying, efflorescence and cryptoflorescence, vegetation and mold, concrete leaching with corrosion product from reinforcement, flooding due to failure of the drainage system, in addition to cracks of varied typology. The deterioration of the state of conservation is sensitive, therefore, carrying out inspections is essential to reveal problems that exist in these special works of art. Studies like this should be reproduced in other urban tunnels in the city of Recife, adding testing to the scope of work in order to contribute to the provision of subsidies that enable the planning and execution of efficient maintenance actions capable of ensuring proper functionality of these works throughout their useful lives.